Decompression of Ludwig's angina in a pregnant patient under bilateral superficial cervical plexus block. Issue 4 (April 2022) - Rahman, Tabishur; Ahmed, Syed; Rahman, Sajjad
Ludwig's angina is defined as a potentially lethal, rapidly spreading cellulitis, involving the sublingual and submandibular spaces, and is manifested by a brawny suprahyoid induration, tender swelling in the floor of the mouth, and elevation and posterior displacement of the tongue. During a life-threatening infection such as Ludwig's angina, the mother and foetus are vulnerable to septicemia and asphyxia. We describe a case of decompression of Ludwig's angina in a 28 weeks pregnant patient under bilateral superficial cervical plexus block. The block, coupled with bilateral mandibular nerve block, provided ample anaesthesia to perform a thorough incision and drainage, including transection of mylohyoid with lowering of the floor of mouth and rapid relief of respiratory obstruction.